Eu, da periferia: a crônica no processo de formação de identidade no espaço escolar - Angelica Natalia Ferreira Gongalves (2019)
Working with language in the classroom usualy means studying its structures and textual production for the sole purpose of "learning to write texts" that will b corrected by the teacher, characterizing writing for writing. Another recurrent situation is the school's distance from social issues beyond its walls, which presents a decontextualized and alienating learning of the reality, causing little reflection of the students on what they experience. In order to contribute to the change of this scenery, this work points out possible actions, based on the studies about the identity by Moita Lopes (2002, 2003), discursive genres and Bakhtins's linguistic interactionism (2003), Literacy studies (KLEIMAN, 1995, STREET, 2014) and Freire's ideas that support critical literacy (FREIRE, 1987). Thus, through the adaptation ofthe poposal of Gender Didactic Project (GUIMARÃES & KERSCH, 2012) to the reality of a 9th grade class from the state school of Palmital neighborhood, in Santa Luzia (MG), a systematic work was proposed with the genre of chronicle, in order to make the students discuss about the local reality and to position themselves critically regarding their formation as subjects in this environment; Moreover, the publication of the texts in a local newspaper, in addition to the production of a jounal of chronicles, effected the social function of the genre, concretizing the PDG. As a result, throughout the workshops students were able to position themselves critically about the neighborhood for instance by relating to the types of violence occurring in that space, which led them to talk about their own identity formation. In addition an analysis of the language capabilities (DOLZ; SCHNEUWLY,2004) used for production of texts has shown significant improvement in this domain by pupils, such as for example the development of a less detailed narrative that requires mor effort from the reader and use of knowledge about the world to undestand the texts.